2004
DOI: 10.1111/j.1601-5029.2004.00070.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral health knowledge and dental health practices among schoolchildren in Jerash district/Jordan

Abstract: Results of this study prove that oral health awareness level among public schoolchildren in Jordan is still poor and needs to be improved. Based upon these findings, the establishment of a long-term school-based oral health education programme in Jordan is highly recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
13
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 19 publications
4
13
2
Order By: Relevance
“…Unlike previous studies by El‐Qaderi (9), Nyandindi (10) and Christensen (11), findings of this study revealed that a high proportion of the children in this study know what causes bleeding gums. The level of knowledge among children in this study on this issue is encouraging.…”
Section: Discussioncontrasting
confidence: 99%
“…Unlike previous studies by El‐Qaderi (9), Nyandindi (10) and Christensen (11), findings of this study revealed that a high proportion of the children in this study know what causes bleeding gums. The level of knowledge among children in this study on this issue is encouraging.…”
Section: Discussioncontrasting
confidence: 99%
“…We found that boys had worse oral hygiene. This result may be related to what has been documented in previous studies about knowledge, attitudes, beliefs, and oral hygiene practices: girls show better understanding than boys 14,37,38 . In the final logistic regression model, younger children had worse levels of oral hygiene.…”
Section: Discussionsupporting
confidence: 76%
“…Girls (84%) outnumbered boys in daily teeth brushing. These findings were comparable to the findings of Mehta et al [6], El Qaderi et al [7], Kuppuswamy et al [8].Almost 92.3% believed that eating sweets leads to dental caries, which was consistent with a study in Nigeria by Ogunrinde et al [9] wherein consumption of sticky, sugary and chocolaty food items were perceived as unhealthy to dental health. In our study 78% of children brushed their teeth using toothbrush and toothpaste which was in accordance to a study by Al-Omiri from Jordan [10] and other studies around the globe.…”
Section: Discussionsupporting
confidence: 82%